POLITENESS STRATEGIES AT FIRST GRADE SDN PAKISTAJI 2 PROBOLINGGO CITY - Yani, Yani; Wafa, Hosnol; Sutrisno, Adi; Tjahyadi, Indra (JURNAL LITERASI, 2024)
The research results is this research was conducted to find out what types of politeness strategies exist in conversations between teachers and students in first grade at SDN Pakistaji 2 during Indonesian language class hours. SDN Pakistaji 2 is a formal school that is unique in terms of communication where students who are predominantly used to using Madurese in communicating are required to be able to use Indonesian properly and correctly when in class. This research uses pragmatic studies, namely the theory of Brown and Levinson (1978). In pragmatic studies there is a theory about politeness which focuses on politeness strategies. There are 5 types of Brown and Levinson theory in this research, namely positive face, negative face, off record, on record and avoidance. This research uses descriptive qualitative methods with recording and transcript techniques to collect and analyze data. The data source comes from audio recordings resulting from observations of conversations between teachers and students in first grade during learning hours. There were 120 data from politeness strategies found in the analysis of audio recordings resulting from observations of conversations between teachers and first grade students at SDN Pakistaji 2 Probolinggo City into 5 types, namely: positive face, negative face, off record, on record, and avoidance. Off record is a type of politeness strategies that is more often found in conversations between Mrs. Ninik and her students with a total of 38 data (31.67%), the second dominant type is on record with a total of 34 data (2.33%), the third type The dominant type is negative face with a total of 33 data (27.5%), the fourth dominant type is a positive face with a total of 12 data (10%), and the last type which is found the least is avoidance with a total of 3 data (2.5 %)..